2022
DOI: 10.1248/cpb.c22-00357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Administration of Q808 on Hippocampal Transcriptome in Healthy Rats

Abstract: Epilepsy treatment with antiepileptic drugs (AEDs) is usually requires for many years. Q808 is an innovative antiepileptic chemical. It exerts effective antiepileptic effect against various epilepsy models. Exploring the gene transcriptomic profile of long-term treatment of Q808 is necessary. In the present study, hippocampus RNAsequencing was performed to reveal the transcriptome profile of rats before and after treatment of Q808 for 28 days. Results confirmed 51 differentially expressed genes (DEGs) between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Although AEDs are widely used in treating SE to prevent further brain damage, they may cause adverse effects such as drowsiness, ataxia, gastrointestinal disturbances, hepatotoxicity, megaloblastic anemia ( Leppik, 1994 ; Perucca, 1996 ; Lin and Kadaba, 1997 ; Sun et al, 2010 ) and potentially life-threatening conditions ( Al-Soud et al, 2003 ; Sun et al, 2010 ). Additionally, a study has reported that AEDs were thought to trigger psychosis in up to 40% of cases ( Thompson, 1999 ; Li et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although AEDs are widely used in treating SE to prevent further brain damage, they may cause adverse effects such as drowsiness, ataxia, gastrointestinal disturbances, hepatotoxicity, megaloblastic anemia ( Leppik, 1994 ; Perucca, 1996 ; Lin and Kadaba, 1997 ; Sun et al, 2010 ) and potentially life-threatening conditions ( Al-Soud et al, 2003 ; Sun et al, 2010 ). Additionally, a study has reported that AEDs were thought to trigger psychosis in up to 40% of cases ( Thompson, 1999 ; Li et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism of Q808 involves modulation of the GABAergic system in specific brain regions, particularly increasing GABA levels in the hippocampus. Q808 has demonstrated effectiveness against various epilepsy models such as seizures induced by pentylenetetrazole (PTZ), isoniazid, thiosemicarbazide, and 3-mercaptopropionic acid ( Li et al, 2022b ). Previous studies have shown that a single dose of Q808 significantly increases GABA ( Olsen, 1981 ; Okada et al, 1989 ; Li et al, 2017 ) in the rat hippocampal region while enhancing the frequency of spontaneous inhibitory postsynaptic currents in the hippocampus ( Li et al, 2017 ; Li et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation